Investigating mildly abnormal serum aminotransferase values. (30th July 2010) - Cobbold, Jeremy F L; Anstee, Quentin M; Thomas, Howard C
Abstract : How do you approach the investigation of a patient with mildly abnormal aminotransferase tests? This article will guide you through diagnosis and assessment of severity